1997
DOI: 10.1023/a:1006595703472
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Many factors influence NFP effectiveness, and these factors must be considered when evaluating published studies and designing future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Staphyloccus aureus was the most common organism isolated (47.1%) in our study, followed by Salmonella typhi in 23.5%, the Salmonella typhi organisms were isolated from the children, with sickle cell disease (Hemoglobin S). This study agrees with other authors who confirmed that Staphylococcus aureus was the most common organism isolated in acute osteomyelitis while Salmonella typhi organism is a common isolate in acute osteomyelitis in children with sickle cell disease (Lamprecht 1997, Karwowska 1998, Dahl 1998, Sadat Ali 1998. Bone aspirate to decompress the bone also help to relieve pain in acute osteomyelitis (Booz 1990).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Staphyloccus aureus was the most common organism isolated (47.1%) in our study, followed by Salmonella typhi in 23.5%, the Salmonella typhi organisms were isolated from the children, with sickle cell disease (Hemoglobin S). This study agrees with other authors who confirmed that Staphylococcus aureus was the most common organism isolated in acute osteomyelitis while Salmonella typhi organism is a common isolate in acute osteomyelitis in children with sickle cell disease (Lamprecht 1997, Karwowska 1998, Dahl 1998, Sadat Ali 1998. Bone aspirate to decompress the bone also help to relieve pain in acute osteomyelitis (Booz 1990).…”
Section: Discussionsupporting
confidence: 92%
“…The surgical intervention is important as it prevents progression of the infection to chronic osteomyelitis (Sadat Ali 1998). Surgical intervention is supported in children with acute osteomyelitis presenting late and in acute osteomyelitis in sickle cell patient (Lamprecht 1997, Sadat Ali 1998.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because NFP methods can be used either to avoid pregnancy or to conceive, assessing users’ intentions is essential to assessing any NFP method’s effectiveness ( 12 , 13 , 18 , 39 ). The CrM educational materials and interactions emphasize radical autonomy for the couple, who decides whether to use it to avoid pregnancy or to conceive ( 28 , 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their use in avoiding pregnancy, FABM or NFP methods are unique among family planning methods in their additional ability to help couples try to time pregnancy ( 12 – 14 ). Indeed, in population-based studies, potential interest in these methods has been greater for the purpose of conceiving than of avoiding conception ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%